Ecohealth research to regionally address agriculture intensification impacts on health and the environment in Southeast Asia and China - Hung Nguyen-Viet; Dinh Xuan Tung; Phuc Pham Duc; Kittayapong, P.; Adismito, W.; Fang, J. (International Livestock Research Institute, 2015)
Ecohealth Field Building Leadership Initiative is a regional operational research network in Southeast Asia and China that focuses on solving human health problems associated with agricultural intensification. FBLI has 3 focus areas, namely research, capacity building and knowledge translation. FBLI gathers researchers, policy makers, community members and other stakeholders from 4 focused countries (China, Indonesia, Thailand and Vietnam). Here we describe the operational research component that focuses on aspects of agriculture intensification on health and the environment including animal waste from pig production (Vietnam), dairy production (Indonesia), pesticide use in vegetable production (China), and health risks in rubber plantation (Thailand). Integrated approaches to the research component including survey, participatory and cross-cutting methods are discussed. The research results from Vietnam and Indonesia showed health and environmental impacts of manure management options, in particular the biogas system and turning waste to value. In Hanam of Vietnam, the health risks from biogas effluent reuse include E. coli infection (19–22% of population exposed) and G. lamblia infection (45–55% of population exposed). In Pangalengan, Indonesia, the Ecohealth approach was used to promote the production of medicinal worm and casting biofertilizer from cow manure as an environmentallyfriendly fertilizer alternative. In Chachoengsao Province of Thailand, key findings include evidences for higher risk of vectorborne diseases (dengue and chikungunya) in rubber plantation areas as well as higher microbial and heavy metal contamination of water and soil. In six villages of three townships in a County of Yunnan Province, China, issues identified were lack of farmer knowledge of pesticides, pesticide abuse, and ineffective policy to reduce pesticide abuse. Pesticide contamination was recorded from 6.1% to 12.7% of vegetables depending on sampling location in the field or market. The findings from 4 countries illustrate how Ecohealth research has been applied in health and agriculture and serve as basis for interventions for reduce health and environmental risks.